A NEW APPROACH TO REDEFINING POLITICAL GEOGRAPHY - Maroofzai, M.; Ahmadi, N. (Farabi Journal of Social Sciences, 2022)
Understanding political geography requires understanding the interaction of geography and politics. Since the design of the University of Political Geography, various definitions and interpretations of this science have been offered, most of which have been subject to the ruling paradigm and the expertise of commentators. New interpretations, influenced by the school of space, have been content with the statement that "political geography studies the interaction of space and politics." Questions and answers in the Afghan university community also indicate that this statement has not been sufficiently understood. Therefore, providing a scientific and practical definition for research and academic fields is inevitable. The present study, with its fundamental nature and interpretive-analytical method, aims to provide a new definition of political geography by using the resources of libraries in the framework of understanding geography and politics in order to recognize the epistemological domains of political geography and the researcher’s entry into borders. Avoid other strings. The results show that territory is more than a spatial container, it is a reflection of human authority, power and control, and issues of territory and territoriality are the basis of geopolitical issues. Based on such characteristics, political geography is a science that defines the political dimensions of geographical space in the form of interaction of power relations (in the dimensions of coexistence, coexistence, tension, conflict and war) with territory (space and land) and territoriality (territorialism, territorialization and Territory) man studies. Keywords: Political Affairs, Political Geography, Territory, Territoriality, Power Relations.